Estrogens and selective estrogen receptor modulators differentially antagonize Runx2 in ST2 mesenchymal progenitor cells. Issue 183 (October 2018) - Amzaleg, Yonatan; Ji, Jie; Kittivanichkul, Donlaporn; E Törnqvist, Anna; Windahl, Sara; Sabag, Elias; Khalid, Aysha B.; Sternberg, Hal; West, Michael; Katzenellenbogen, John A.; Krum, Susan A.; Chimge, Nyam-Osor; et al.
Graphical abstract: Highlights: Estrogen typically inhibits Runx2 in osteoblast progenitors. Estrogen does not inhibit Runx2 at particular genes and concentrations. Bimodal effect of increasing estrogen concentrations on osteoblast differentiation. SERMs poorly mimic the bimodal effect of estrogen in pre-osteoblasts. SERMs closely mimic estrogen in pre-osteoclasts. Abstract: Estrogens attenuate bone turnover by inhibiting both osteoclasts and osteoblasts, in part through antagonizing Runx2. Apparently conflicting, stimulatory effects in osteoblast lineage cells, however, sway the balance between bone resorption and bone formation in favor of the latter. Consistent with this dualism, 17ß-estradiol (E2) both stimulates and inhibits Runx2 in a locus-specific manner, and here we provide evidence for such locus-specific regulation of Runx2 by E2 in vivo . We also demonstrate dual, negative and positive, regulation of Runx2-driven alkaline phosphatase (ALP) activity by increasing E2 concentrations in ST2 osteoblast progenitor cells. We further compared the effects of E2 to those of the Selective Estrogen Receptor Modulators (SERMs) raloxifene (ral) and lasofoxifene (las) and the phytoestrogen puerarin. We found that E2 at the physiological concentrations of 0.1–1 nM, as well as ral and las, but not puerarin, antagonize Runx2-driven ALP activity. At ≥10 nM, E2 and puerarin, but not ral or las, stimulate ALP relative to the activity measured at 0.1–1 nM. Contrasting the difference between E2 and SERMs in ST2 cells, they all shared a similar dose-response profile when inhibiting pre-osteoclast proliferation. That ral and las poorly mimic the locus- and concentration-dependent effects of E2 in mesenchymal progenitor cells may help explain their limited clinical efficacy.